2015
DOI: 10.5352/jls.2015.25.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MRSA Properties of Prodigiosin from Serratia sp. PDGS 120915

Abstract: Prodigiosin, a member of natural red pigment family, is produced by Serratia marcescens, and characterized by a common pyrrolylpyrromethane skeleton. This pigment has been reported with the effects of anticancer, immunosuppressant, antifungal, and algicidal activities. Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of hospital infections. In this study, anti-MRSA properties of prodigiosin isolated from Serratia sp. PDGS 120915 were investigated. We identified and purified prodigiosin using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…In this study, the MIC value of prodigiosin ranged from 2.5 to 5 mg/L for all S. aureus isolates. This was inconsistent with previously reported MIC values, which were in the range of 0.25–32 mg/L ( Ji et al, 2015 ; Danevčič et al, 2016b ; Suryawanshi et al, 2017 ; Wang B. et al, 2022 ; Wang Y. J. et al, 2022 ; Yan et al, 2023 ). Possible reasons for the wide range of MIC values reported in the literature may be prodigiosin samples obtained from different strains, different purification methods, as well as different methods for measuring MIC values and different testing strains.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the MIC value of prodigiosin ranged from 2.5 to 5 mg/L for all S. aureus isolates. This was inconsistent with previously reported MIC values, which were in the range of 0.25–32 mg/L ( Ji et al, 2015 ; Danevčič et al, 2016b ; Suryawanshi et al, 2017 ; Wang B. et al, 2022 ; Wang Y. J. et al, 2022 ; Yan et al, 2023 ). Possible reasons for the wide range of MIC values reported in the literature may be prodigiosin samples obtained from different strains, different purification methods, as well as different methods for measuring MIC values and different testing strains.…”
Section: Discussioncontrasting
confidence: 99%
“…coli was 103.4 ± 6.3 μg/mL [ 25 ], purified prodigiosin from Serratia sp. PDGS 120915 has an MIC value of 32 μg/mL against MRSA [ 76 ] and purified prodigiosin from S . marcescens UFPEDA 398 had low MIC values (1.0–4.0 μg/mL) against eighteen oxacillin-resistant S .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MIC of prodigiosin purified from Vibrio ruber DSM14379 towards E. coli was 103.4 ± 6.3 μg/mL [25], purified prodigiosin from Serratia sp. PDGS 120915 has an MIC value of 32 μg/mL against MRSA [76] and purified prodigiosin from S. marcescens UFPEDA 398 had low MIC values (1.0-4.0 μg/mL) against eighteen oxacillin-resistant S. aureus (ORSA) clinical strains [58]. Although the absorption spectra, HPLC and LC-MS/MS analyses (Figs 2 and 3) showed that prodigiosin is a predominant compound in the crude extract, nevertheless, the higher MIC value may likely be a result of minor impurities within the crude prodigiosin extract which could have impeded the action of prodigiosin or its interaction with the bacterial membrane, thus, requiring higher prodigiosin concentrations to inhibit bacterial growth.…”
Section: Plos Onementioning
confidence: 99%
“…The combination of natural pigments with traditional antibiotics may represent a strategy to counteract the spread of superbugs. In this context, PG in combination with β‐lactamic antibiotics showed a synergistic effect against a MRSA strain 90 .…”
Section: Biotechnological Applications Of Bacterial Pigmentsmentioning
confidence: 91%